Implementasi Peraturan Gubernur Riau Nomor 56 Tahun 2016 Tentang Pedoman Pengelolaan Aplikasi Perkantoran Secara Elektronik (E-Office) di Dinas Tenaga Kerja dan Transmigrasi Provinsi Riau - Habib Caesar Artanugraha; Geovani Meiwanda (Jurnal Ilmiah Wahana Pendidikan, 2023)
The Riau Province Manpower and Transmigration Office made one of the changes, namely by improving office administration processes by utilizing information and communication technology by implementing an electronic office or e-Office. E-Office is a service that aims to simplify the process of office administration activities that are carried out electronically. In addition to minimizing the use of paper, e-office is also useful for facilitating data storage and data processing in the office, and of course, e-office can be accessed anywhere and anytime. The purpose of this study was to determine the implementation of Riau governor regulation number 56 of 2016 regarding guidelines for managing office applications electronically (e-office) in the Department of Manpower and Transmigration of Riau Province. The type of research used is qualitative research and data collection techniques based on interviews and documentation. This study uses Charles O. Jones’s Theory which uses 3 indicators, namely Organization, Interpretation, and Application. The results of this study are that there are still several obstacles that occur in its implementation, so the use of e-office is still not optimal at the Manpower and Transmigration Office of Riau Province where there is still low employee initiative in using e-office because employees are still comfortable in manual work culture, then the signature of the head of a service which is still not able to be used electronically also causes the Riau Province Manpower and Transmigration Service to be unable to send outgoing letters via e-office, furthermore, the office administration has not been fully backed up at the Office of Manpower and Riau Province's transmigration into e-office applications has resulted in the implementation of e-office not running optimally. So these various factors and needs must be corrected and implemented to achieve an optimal and maximal application.